First ways to find out breast cancer by Breast Self-Examination (BSE) - Susi Muryani; Nurhakim Yudhi Wibowo; Prayogi Ning Tyastuti (Media Keperawatan Indonesia, 2024)
Breast self-examination (BSE) or SADARI is one of the first ways to find out breast cancer by seeing and feeling if there are abnormalities. The Indonesian Ministry of Health in 2022 said that the incidence of breast cancer in Indonesia was 26 per 100 thousand population, and 70% were detected at an advanced stage and could result in death. Delays in early detection of breast cancer due to lack of knowledge and information. Health education about BSE is important as an effort to prevent breast cancer. The purpose of this study was to determine the effect of BSE health education on knowledge about early detection of breast cancer in SMA Negeri 01 Jatibarang. This type of research uses a quasi-experimental design with a one-group pre-post test design without control. The sample in this study was female students in grades 10 and 11, who were taken using the simple random sampling technique with as many as 78 respondents. The Wilcoxcon signed rank test statistical test showed a p-value of 0.000 <0.05, which means that there is an effect of health education on knowledge using the demonstration method. Based on this research, it is expected that young women can apply knowledge and implement BSE prevention as an effort to detect early breast cancer.